Characterization of novel inhibitors of histone acetyltransferases - Eliseeva, Elena D; Valkov, Vassil; Jung, Manfred; Jung, Mira O (Molecular cancer therapeutics, 2007)
Modification of proteins by histone acetyltransferases (HAT) or histone deacetylases plays an important role in the control of gene expression, and its dysregulation has been linked to malignant transformation and other diseases. Although histone deacetylase inhibitors have been extensively studied and several are currently in clinical trials, there is little information available on inhibitors of HATs (HATi). Starting from the natural product lead HATi anacardic acid, a series of 28 analogues was synthesized and investigated for HAT-inhibitory properties and effects on cancer cell growth. The compounds inhibited up to 95% HAT activity in vitro, and there was a clear correlation between their inhibitory potency and cytotoxicity toward a broad panel of cancer cells. Interestingly, all tested compounds were relatively nontoxic to nonmalignant human cell lines. Western blot analysis of MCF7 breast carcinoma cells treated with HATi showed significant reduction in acetylation levels of histone H4. To directly show effect of the new compounds on HAT activity in vivo, MCF7 cells were cotransfected with the p21 promoter fused to firefly luciferase and a full-length p300 acetyltransferase, and luciferase activity was determined following treatment with HATi. Significant inhibition of p300 activity was detected after treatment with all tested compounds except one. Effects of the new HATi on protein acetylation and HAT activity in vivo make them a suitable tool for discovery of molecular targets of HATs and, potentially, for development of new anticancer therapeutics.